Pengaruh Produk Domestik Bruto (PDB), Kurs Dollar Amerika Serikat dan Inflasi Terhadap Impor Sayuran Indonesia Kurun Waktu 1994-2013 - Candra Wati, Anak Agung Istri Diah; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
International trade gives a great influence for each country. The needs of each different country with different crops also be cause the country needs other countries to meet domestic demand. This study aims to determine how the effect of GDP, the US dollar exchange rate and inflation on imported vegetables Indonesia. The data period 1994-2013 used secondary data with analysis technique is multiple linear regression using Eviews program. Based on the results of simultaneous analysis known that all independent variables a significant effect on the import of vegetables Indonesia, while partially GDP provide a positive and significant effect while the US dollar exchange rate gives a negative and significant effect. But inflation is not a significant effect on the import of vegetables Indonesia for vegetable importers do not pay attention to the percentage of the rate of inflation because vegetables are foods that are needed by our body.
Keywords: GDP, US Dollar exchange rate, inflation, imports